Penanaman Karakter Demokratis Melalui Pembiasaan Dalam Pembelajaran Pendidikan Pancasila Di Sekolah Dasar - Setyowati, Jeny; Utomo, Arief Cahyo (Jayapangus Press, 2024)
Democratic character is essential for students because it will affect how students think and act in everyday life. Therefore, schools need to instil democratic values ​​from an early age. The fourth-grade teacher of SD Negeri Gondang 1 has tried to instil democratic character by implementing internalised habits in Pancasila education learning. This study aims to describe the application of habits in Pancasila education learning to instil students' democratic character and to find out the obstacles faced in its implementation. This study uses a qualitative descriptive approach. Data collection techniques use observation, interviews, and documentation. Data analysis in this study, namely data reduction, data presentation, and conclusion. Validity tests use triangulation techniques and source triangulation. The study results indicate that the instillation of democratic character is carried out in Pancasila education learning through habits that are carried out, including : 1) Routine activities such as group activities, presentations, and delivering responses; 2) Spontaneous activities include discussions when there are differences of opinion and teacher reprimands; and 3) Role models such as teachers motivate and show appreciation to students. The most significant democratic character indicators in habituation activities are getting used to deliberation, providing opportunities to express opinions, and respecting opinions or criticism. The obstacles were differences in student backgrounds and low awareness of the need to carry out habituation activities properly. To overcome these obstacles, teachers try to provide special assistance to students.